EFFECTIVENESS OF DIMENSIONS EXECUTIVE MANAGEMENT APPLICATIONS TO ACHIEVE COMPETITIVE ADVANTAGES - Saad Faysil Mahmoud (Scholars Digest Publishing, 2024)
This study highlights the importance of the impact of Executive Management (EM) dimensions (Environmental-EN, Economic-EC, Social-SO) on Competitive (CO) advantage. This study focused on emphasizing the variables to achieve high-quality production. A questionnaire form was used to collect the data needed by the researcher for this study. Their number reached (142), and (6) questionnaires were incorrect, valid questionnaires were obtained (136) in Diwaniyah Textile Factory / Iraq. In this study, the researcher used SPSS & Smart-PLS 4 statistical analysis to obtain the required results. The researcher in this study reached positive results with high efficiency, and the dimensions of executive management focus on developing competitive advantage in the organization. This study also focused on important recommendations to benefit from to develop the relationship between the dimensions of executive management and competitive advantage.
Keywords: dimensions of executive management, competitive advantage, environmental, economic, social.